A randomized phase 2a efficacy and safety trial of the topical Janus kinase inhibitor tofacitinib in the treatment of chronic plaque psoriasis. (8th July 2013) - Ports, W.C.; Khan, S.; Lan, S.; Lamba, M.; Bolduc, C.; Bissonnette, R.; Papp, K.
<x xml:space="preserve">Abstract</x> What's already known about this topic? Janus kinase (JAK) signalling has been implicated in the pathogenesis of psoriasis. Tofacitinib (CP‐690, 550) is a novel, small‐molecule JAK inhibitor in development for the treatment of several inflammatory diseases: it has demonstrated efficacy in a phase 2b study in moderate‐to‐severe plaque psoriasis when given orally. Topical therapy is the more commonly used therapeutic option for psoriasis, but there is a need for improved topical treatments. What does this study add? In this phase 2a study, tofacitinib in an ointment formulation demonstrated efficacy, systemic safety and local tolerability during 4 weeks of treatment in patients with mild‐to‐moderate chronic plaque psoriasis. Dermal penetration of tofacitinib, a small‐molecule, was demonstrated. Topical application of tofacitinib has the potential to provide an additional therapeutic option for patients with plaque psoriasis.